Dumb software agents on an experimental asset market - Jens Großklags; Carsten Schmidt; Jonathan Siegel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
We have analyzed the impact of agents and their trading strategies on an experimental electronic market. Therefore, we added an XML-interface to an existing electronic market and implemented artificial agents which acted as elements of disturbance in the trading process. These artificial traders applied simple and constant strategies which may sometimes appear to be rational or random to the eyes of other traders. We then stepped back and recorded the reaction of the electronic market.
urn:nbn:de:kobv:11-10048222
Keywords: 330; XML; double auction; negotiation